Intake Assessment and Diagnostic Accuracy of Attention Deficit Hyperactivity Disorder diagnostic Scale Being Developed for Children in Nepal - Devkota, Narmada; Subba, Shishir; Sharma, Nandita; Devkota, Janardan (Journal of Nepal Health Research Council, 2020)
Background: Establishment of accurate diagnosis of participants is vital before starting the development of diagnostic scale. The aim of this study was to develop psychometrically sound Attention Deficit Hyperactivity Disorder diagnostic scale for children. Methods: Informed consent was taken. Initial diagnosis of Attention Deficit Hyperactivity Disorder was made by using Diagnostic and Statistical Manual-5. Socio-demographic data were obtained. Behavior observation, parental information and teacher’s report were also analyzed. Then, Kiddie-Schedule for Affective disorders and Schizophrenia, Child and Adolescent Symptoms Inventory, Stroop Color and word test were done to obtain confirmatory data. Verbatim collection was done to develop the culture specific items. Likewise, standardization was doneResults: Accurate diagnosis was established with the help of various tools and techniques. Comorbid conditions were excluded. Diagnostic accuracy was assessed where reliability of each item was ? 0.90; whereas, sensitivity and specificity were 97.0% and 96.6%, respectively with cut off score of 38.5. All items are highly co-related with Attention Deficit Hyperactivity Disorder items of Child and Adolescent Symptoms Inventory-5.Conclusions: Results clearly indicated that diagnostic accuracy values of this scale is high.Keywords: Attention deficit hyperactivity disorder; assessment; diagnostic accuracy; specificity-sensitivity